2008
DOI: 10.1152/ajpregu.90429.2008
|View full text |Cite
|
Sign up to set email alerts
|

Thermal tolerance of contractile function in oxidative skeletal muscle: no protection by antioxidants and reduced tolerance with eicosanoid enzyme inhibition

Abstract: Mechanisms for the loss of muscle contractile function in hyperthermia are poorly understood. This study identified the critical temperature, resulting in a loss of contractile function in isolated diaphragm (thermal tolerance), and then tested the hypotheses 1) that increased reactive oxygen species (ROS) production contributes to the loss of contractile function at this temperature, and 2) eicosanoid metabolism plays an important role in preservation of contractile function in hyperthermia. Contractile funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 64 publications
1
11
0
1
Order By: Relevance
“…In fast-twitch extensor digitorum longus fibres the increased ROS production at high temperature was accompanied by a reduction in tetanic force, which was counteracted by application of antioxidant or reducing agents (van der Poel & Stephenson, 2002;Edwards et al 2007). Conversely, a force depression at high temperature, which was not prevented by antioxidants or reversed by reducing agents, has been described in slow-twitch peroneus longus fibres and strips of diaphragm muscles (van der Poel & Stephenson, 2002;Oliver et al 2008). In the present study, we observed no decrease in tetanic force in soleus fibres when the temperature was increased from 37 to 43 • C. Furthermore, tetanic force was not decreased in FDB when the temperature was increased from 31 to 37 • C. Thus, intact soleus and FDB fibres can tolerate a temperature ∼6 • C above the in situ temperature without displaying any decrease in tetanic force production.…”
Section: Discussionmentioning
confidence: 99%
“…In fast-twitch extensor digitorum longus fibres the increased ROS production at high temperature was accompanied by a reduction in tetanic force, which was counteracted by application of antioxidant or reducing agents (van der Poel & Stephenson, 2002;Edwards et al 2007). Conversely, a force depression at high temperature, which was not prevented by antioxidants or reversed by reducing agents, has been described in slow-twitch peroneus longus fibres and strips of diaphragm muscles (van der Poel & Stephenson, 2002;Oliver et al 2008). In the present study, we observed no decrease in tetanic force in soleus fibres when the temperature was increased from 37 to 43 • C. Furthermore, tetanic force was not decreased in FDB when the temperature was increased from 31 to 37 • C. Thus, intact soleus and FDB fibres can tolerate a temperature ∼6 • C above the in situ temperature without displaying any decrease in tetanic force production.…”
Section: Discussionmentioning
confidence: 99%
“…Group 1 muscles were subjected to twitches at 1/min throughout the remaining 2 h protocol. This low level stimulation has previously been shown not to fatigue isolated muscles and was used to continually monitor contractile function during the heat stimulus, as described in previous studies from our laboratory (51,72). Following completion of the protocol the muscles were quickly blotted on tissue paper, weighed, flash-frozen in liquid nitrogen, and stored at Ϫ80°C for subsequent analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Within muscle, phospholipases (PLAs) catalyze the metabolism of membrane phospholipids of several organelles, producing eicosanoids that function in an autocrine manner to activate the GTPase, Rac, and production of superoxide (O 2 .À ). This heat-induced production of ROS within myocytes appears to be functionally important in acute exercise responses via regulation of cell volume and force production (King et al, 2016;Oliver et al, 2008) and adaptively in stimulating upstream regulators of PGC1a (Tamura et al, 2014).…”
Section: Reviewmentioning
confidence: 99%